Expression of Cyp2c/Cyp2j subfamily members and oxylipin levels during LPS-induced inflammation and resolution in mice - Graves, Joan P. (FASEB J, 2019)
Inflammatory stimuli, such as bacterial LPS, alter the expression of many cytochromes P450. CYP2C and CYP2J subfamily members actively metabolize fatty acids to bioactive eicosanoids, which exhibit potent anti-inflammatory effects. Herein, we examined mRNA levels of the 15 mouse Cyp2c and 7 mouse Cyp2j isoforms in liver, kidney, duodenum, and brain over a 96-h time course of LPS-induced inflammation and resolution. Plasma and liver eicosanoid levels were also measured by liquid chromatography with tandem mass spectrometry. Expression changes in Cyp2c and Cyp2j isoforms were both isoform and tissue specific. Total liver Cyp2c and Cyp2j mRNA content was reduced by 80% 24 h after LPS but recovered to baseline levels by 96 h. Total Cyp2c and Cyp2j mRNA in kidney (−19%) and duodenum (−64%) were reduced 24 h after LPS but recovered above baseline by 72 h. Total Cyp2c and Cyp2j mRNA content in brain was elevated at all time points after LPS dosing. Plasma eicosanoids transiently increased 3–6 h after administration of LPS. In liver, esterified oxylipin levels decreased during acute inflammation and before recovering. The biphasic suppression and recovery of mouse Cyp2c and Cyp2j isoforms and associated changes in eicosanoid levels during LPS-induced inflammation and resolution may have important physiologic consequences.—Graves, J. P., Bradbury, J. A., Gruzdev, A., Li, H., Duval, C., Lih, F. B., Edin, M. L., Zeldin, D. C. Expression of Cyp2c/Cyp2j subfamily members and oxylipin levels during LPS-induced inflammation and resolution in mice.